Kota Samarahan Municipal Council / Shirley Mula Collin - Collin, Shirley Mula (University Technology MARA Sarawak, 2020)
At first, Kota Samarahan Municipal Council began as a small area located under the Kuching District. Later, the Municipal Council of Kota Samarahan (MPKS) was gazette as a Local Council in Sarawak under the Local Authorities Ordinance Cap. 117 on January 1, 1985. The Municipal Council of Samarahan is a body called the Local Authority, subject to the jurisdiction of the Ministry of National Housing and Local Government. The Municipal Council of the Kota Samarahan exercises the powers conferred by the Local Authority Ordinance and the Local Authority By-Law under its jurisdiction. The locals are subject to the authority of the Local Authorities.